THEORETICAL AND METHODOLOGICAL ISSUES OF THE CONCEPT OF THE WAGE FUND - Sarvar Khudoynazarovich Ergashev (International Scientific and Current Research Conferences, 2025)
This article examines the concepts of remuneration and the wage fund from theoretical, methodological, and legal perspectives. Based on the research, the author proposes original definitions of both the remuneration fund and the wage fund, along with a detailed composition of their elements. It is argued that this composition can serve as a basis for applying various financial reporting and tax-related incentives within enterprises.